Combine harvesting: spreading success in South East Asia - CGIAR Research Program on Rice (2019)
IRRI spearheaded facilitation of technology improvement and multi-sectoral collaboration through public-private partnerships. Activities involved assessment of harvesting systems and promotion of mechanized options to address labor shortage and high cost of traditional harvesting. Business models were established with special focus on marginalised groups, women and youth.Analysis of the existing harvesting system within a value chain context, harvesting and postharvest losses, identification and demonstration of mechanised options and stakeholder analysis conducted.Used Life Cycle assessment for sustainability criteria in different harvesting systems.